Activity participation home and away – examining the spillover theory among families on holiday. Issue 2 (3rd April 2017) - Sthapit, Erose; Björk, Peter
Abstract: A review of the literature on family leisure travel indicates an emphasis on the spectacular and exotic, with little empirical investigation on everyday behaviours retained while on vacation. The present study examines possible spillovers from the home to the tourism setting by examining the influence of leisure involvement, leisure habit, and psychological commitment on vacation behaviour. Data were collected from family vacationers to Rovaniemi, Finland, and 215 valid responses were used in the analysis. The findings indicate a positive relationship between leisure involvement, leisure habit, and vacation behaviour, while psychological commitment did not mediate the relationship between the constructs. The study offers evidence that visitors may exhibit similar behaviours in both their home and holiday environments in the family leisure travel context.